Design of Student Worksheets Based on Polya’s Problem-Solving Process to Facilitate Students’ Reflective Thinking Skills - Nurhuda Teapon; Yaya S. Kusumah; Elmawati; Marwa M. Sehe (Universitas Cokroaminoto Palopo, 2025)
Abstract This research is motivated by the conditions in the field, which show that the Student Worksheets (LKPD) circulating in schools generally contain learning activities that do not encourage students' reflective thinking skills and student learning motivation. This condition results in suboptimal student engagement in the learning process, causing learning to remain passive and lacking in challenge. Therefore, this study aims to produce student worksheets based on Polya's problem-solving process as an effort to facilitate students' reflective thinking skills. This research method uses the ADDIE development method, which focuses on four initial stages: Analysis, Design, Development, and Implementation. The validated LKPD was then tested on a limited basis in one class. Participants in this study were 25 grade X students at a high school in Bandung City. Data collection was carried out using validation sheets and teacher and student response questionnaires. Based on the research results, it can be concluded that the developed LKPD based on Polya's Problem Solving Process is worthy of being continued to the next stage, namely the evaluation stage, as an effort to facilitate students' reflective thinking skills.